The Influence of Technological and Marketing Capabilities on MSME Performance with Organizational Learning as a Mediating Variable - Sieradianto Angelia, Dinda Ayu; Ardiansyah, Angga; Muttaqin, Rahmat Bahaul (Faculty of Economics and Business, Universitas Klabat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are key contributors to economic development, especially in emerging markets. However, MSMEs often struggle to sustain and improve their performance amid dynamic market conditions and increasing global competition. This study investigates the integrated effects of organizational learning, marketing capability, and technological capability on MSME performance in Indonesia, a context where prior research has typically examined these factors in isolation. Guided by the dynamic capabilities framework, this study aims to fill the gap by analyzing the synergy among these three capabilities. A quantitative approach was employed, with data collected from 100 MSME actors through an online survey using a structured questionnaire measured on a five-point Likert scale. Structural Equation Modeling (SEM) using SmartPLS 3.2 was used to analyze the data. The results show that organizational learning significantly influences both marketing and technological capabilities. Moreover, technological capability positively affects MSME performance, whereas marketing capability does not have a statistically significant impact on performance. These findings highlight the crucial role of organizational learning as a foundation for capability development and suggest that technological adoption is a key driver of competitive performance in the digital era. The study offers practical insights for MSMEs aiming to improve long-term sustainability through integrated strategic capability development.